Pembangunan Sistem Informasi Pembayaran Biogas Skala Rumah Tangga Berbasis Web di Desa Claket Kecamatan Pacet Kabupaten Mojokerto - Andrean Bagus Mahendra; Bayu Priyambadha; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The scarcity of subsidized LPG is become the biggest problem for the people in lower to middle class. This scarcity triggered by the increasing of the community that used LPG. In addition, scarcity had been caused by a fraud of some people whose shouldn't use a subsidized LPG. For the some people whose the cattle breeders in Claket Village isn't unfortunate this problem, because they are recycling cow manures become to a biogas. Than, the product of biogas can be alleviate for the breeders themselves and for the neighbours if they needed. However, there's nothing cost controller had been used to control the user for using biogas, so they needed a tool that can be used to control a biogas payment. Therefore, the solution was offered by make a web-based biogas payment system by applying the internet of things concept. The internet of things concept is built with the NodeMCU based module and it's working in MQTT network protocol as a bridge of data communication. This device will be used to detect a biogas flows and converting into data. Furthermore, it will be send and process into biogas payment system. Finally, several stages of testing are carried out on the system which results in a valid percentage of 100%.